2015
DOI: 10.3390/medicines2030220
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Synergistic Extract Combinations from Terminalia Catappa, Terminalia Mantaly and Monodora tenuifolia Against Pathogenic Yeasts

Abstract: Mycoses caused by Candida and Cryptococcus species, associated with the advent of antifungal drug resistance have emerged as major health problems. Improved control measures and innovative therapies are needed. This paper describes results from the screening of bio-guided fractionated extracts alone and combinations of Terminalia catappa, Terminalia mantaly and Monodora tenuifolia harvested in Cameroon. Crude ethanolic, hydro-ethanolic and aqueous extracts and bio-guided fractions were screened for antifungal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Subfraction combinations of Terminalia catappa, Terminalia mantaly, and Monodora tenuifolia showed synergistic interactions against C. albicans, C. glabrata, C. parapsilosis, and C. neoformans isolates. Synergistic combination between M. tenuifolia and T. mantaly subfractions also showed fungicidal effects against most tested strains [168].…”
Section: Synergistic Action Between Phytochemicals and Antifungalsmentioning
confidence: 86%
“…Subfraction combinations of Terminalia catappa, Terminalia mantaly, and Monodora tenuifolia showed synergistic interactions against C. albicans, C. glabrata, C. parapsilosis, and C. neoformans isolates. Synergistic combination between M. tenuifolia and T. mantaly subfractions also showed fungicidal effects against most tested strains [168].…”
Section: Synergistic Action Between Phytochemicals and Antifungalsmentioning
confidence: 86%
“…Numerous scientific studies have explored the antimicrobial, antiprotozoal, antidiarrheal, anti-inflammatory, antitumor and wound healing activities; which can be attributed to phytochemicals present in the plant [ 1 ]. A survey of the literature has revealed that the Terminalia genus, TM included; possesses a variety of bioactive phytochemical constituents, such as tannins, pentacyclic triterpenes, glycoside derivatives, flavonoids and phenolic compounds [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, extracts from medicinal plants such as Terminalia mantaly (Combretaceae) are widely used by traditional healers to control diverse infections or associated symptoms, including but not limited to dysentery, gastroenteritis, hypertension, diabetes, and oral, dental, cutaneous and genital affections [ 8 ]. Previous studies on the extracts of this plant have showed antibacterial and antifungal properties, but their chemical compositions have not yet been determined [ 9 ]. However, phytochemical studies of other species of the genus Terminalia have reported the presence of flavonoids, terpenoids and their glycosides derivatives, tannins, flavonones and chalcones [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%